(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2019)
In this study, an attempt was made to assess quality as well as pharmaceutical equivalence of six brands of metformin hydrochloride tablets marketed in Addis Ababa using in vitro methods. Friability, disintegration, dissolution and assay for the content of active ingredients were evaluated using the methods described in the United States pharmacopeia (2007). All the brands of metformin hydrochloride tablets complied with the official specification for hardness, friability, disintegration and assay. Five brands of metformin hydrochloride complied with the USP dissolution tolerance limits but Metformin Denk failed to release the stated amount. Statistical comparison for in vitro drug release indicates that some of the products of metformin hydrochloride tablets showed significant difference (P<0.05), indicating difference in their in vitro drug release that might affect the in vivo bioavailability and the bioequivalence of the products. Bangladesh J. Sci. Ind. Res.54(2), 169-176, 2019